(Not so) easy come, (still) easy go? Footloose multinationals revisited - Pierre Blanchard; Emmanuel Dhyne; Catherine Fuss; Claude Mathieu (National Bank of Belgium, 2012)
This paper revisits the "footloose" nature of multinational firms (MNFs) hypothesis. Using firm-level data for Belgium over the period 1997-2008, we rely on a Probit model and take into account the endogeneity of the determinants of firm exit. Our results may be summarised as follows. First, the unconditional exit probability of MNFs is lower than that of domestic firms. Second, controlling for firm and sector characteristics - firm age, Total Factor Productivity, sunk costs, size, competition on the product market, sector-level value added growth, and sector dummies - the difference between the exit probability of MNFs and domestic firms becomes positive. Third, our results show that MNFs have a lower sensitivity to sunk costs and size than do domestic firms, which may be interpreted as lower exit barriers due to greater possibilities of relocating tangible and intangible assets to foreign affiliates.
Keywords: D22; F23; 330; firm exit; multinationals; Total Factor Productivity; sunk costs; panel data; Probit model; Multinationales Unternehmen; Produktivität; Liquidation; Sunk Costs; Probit-Modell; Belgien